Undifferentiated Pleomorphic Sarcoma of the Duodenal Papilla: A Rare Case and Worth Discussing History - Wang, Jianlong; Liu, Bin; Hou, Jiachao; Li, Tao (Frontiers in Surgery, 2022)
Abstract Background: Undifferentiated pleomorphic sarcoma (UPS) is a malignant tumor that originates in the mesenchymal tissue and is common in the extremities and retroperitoneum. Primary UPS of the duodenum is extremely rare, and that of the duodenal papilla has not been reported up to now. Case presentation: In this report, we depicted the clinical and imaging characteristics of a 48-year-old man presenting with a primarily duodenal papilla UPS. The patient complained of melena and upper gastrointestinal bleeding. He had undergone choledochectomy and choledochaljejunostomy for obstructive jaundice 8 years before admission. Endoscopic examination after admission confirmed a mass located at the duodenal papilla, then the duodenal papillectomy was performed, and the histopathology report confirmed the diagnosis of UPS. The patient refused further treatment and died 2 months later due to tumor recurrence and intrahepatic metastasis. Conclusions: As we know, this is the first report of UPS in the duodenal papilla. The unpredicted behavior of these tumors warrants a careful plan considering their indolent nature and possible recurrence and metastasis. Surgical procedures are controversial. Elderly people should undergo gastroscopy regularly to detect and treat these rare tumors as early as possible to improve their long-term prognosis.